BUNGA BANK DALAM PERSPEKTIF ISLAM (STUDI PENDAPAT NAHDLATUL ULAMA DAN MUHAMMADIYAH) - Abdul Salam (Universitas Alma Ata, 2013)
Abstract One of the problems is crowded and is still being debated in the Islamic economy is a matter of usury which is forbidden in the Koran . This debate mainly focused on what is really meant by riba in the Qur'an and how the economy of the Muslims who are held in the middle of the current capitalist economy and modern banking practices that require interest in economic activity .In existential presence of banking institutions can not be separated from economic problems of Muslims as a whole . Muslims who live in the modern system of value-free economy can not escape the